The absence of SigX results in impaired carbon metabolism and membrane fluidity in Pseudomonas aeruginosa. Issue 1 (December 2018) - Fléchard, Maud; Duchesne, Rachel; Tahrioui, Ali; Bouffartigues, Emeline; Depayras, Ségolène; Hardouin, Julie; Lagy, Coralie; Maillot, Olivier; Tortuel, Damien; Azuama, Cecil; Clamens, Thomas; Duclairoir-Poc, Cécile; et al.
Abstract InPseudomonas aeruginosa, SigX is an extra-cytoplasmic function σ factor that belongs to the cell wall stress response network. In previous studies, we made the puzzling observation thatsigX mutant growth was severely affected in rich lysogeny broth (LB) but not in minimal medium. Here, through comparative transcriptomic and proteomic analysis, we show that the absence of SigX results in dysregulation of genes, whose products are mainly involved in transport, carbon and energy metabolisms. Production of most of these genes is controlled by carbon catabolite repression (CCR), a key regulatory system than ensures preferential carbon source uptake and utilization, substrate prioritization and metabolism. The strong CCR response elicited in LB was lowered in asigX mutant, suggesting altered nutrient uptake. Since the absence of SigX affects membrane composition and fluidity, we suspected membrane changes to cause such phenotype. The detergent polysorbate 80 (PS80) can moderately destabilize the envelope resulting in non-specific increased nutrient intake. Remarkably, growth, membrane fluidity and expression of dysregulated genes in thesigX mutant strain were restored in LB supplemented with PS80. Altogether, these data suggest that SigX is indirectly involved in CCR regulation, possiblyvia its effects on membrane integrity and fluidity.